Síntese e caracterização de tungstato de ferro (FeWO4) e tungstato de zinco (ZnWO4) para aplicações tecnológicas - Severo, Eric da Cruz (2015)
In this study, two tungsten-based oxides, iron tungstate (FeWO4) and zinc tungstate (ZnWO4), were synthesized by the routes microwave-assisted hydrothermal and solvo-hidrothermal, respectively. The iron tungstate oxide was used as a catalyst in heterogeneous photo-Fenton reaction for removal of Amaranth dye, whereas the zinc tungstate was used as a support for the immobilization of inulinase by adsorption process. Both materials produced were characterized by techniques such as X-ray diffraction (XRD), nitrogen adsorption-desorption analysis by Brunauer-Emmett-Teller method (BET), Fourier transform infrared spectroscopy (FTIR) and particle size distribution analysis by laser diffraction. For heterogeneous photo-Fenton reaction, an experimental design was used to study the effect of variables such as pH, hydrogen peroxide concentration and dye concentration on the degradation efficiency of Amaranth dye. The inulinase immobilization on the ZnWO4 oxide was investigated in two temperatures. According to the characterization results, both synthesized material has a porous structure and high crystallinity. The FeWO4 oxide showed a satisfactory ability to degrade amaranth dye, and under the optimum reaction conditions, 97% decolorization and 58% mineralization were obtained. Furthermore, the efficiency and stability of this catalyst were maintained high after five cycles of reuse. The ZnWO4 oxide showed a satisfactory inulinase adsorption, where the best result was found to be 605 U.g-1 at 30 oC.